2016
DOI: 10.1186/s12936-016-1603-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in malaria prevalence and increase in malaria awareness in endemic districts of Bangladesh

Abstract: BackgroundMalaria is endemic in 13 districts of Bangladesh. A baseline malaria prevalence survey across the endemic districts of Bangladesh was conducted in 2007, when the prevalence was reported around 39.7 per 1000 population. After two rounds of Global Fund to Fight AIDS, Tuberculosis and Malaria (GFATM)-funded intervention by the National Malaria Control Programme (NMCP) and a BRAC-led NGO consortium, a follow-up survey was conducted across the malaria-endemic districts of Bangladesh to measure the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
3
23
5
Order By: Relevance
“…This has been shown previously [ 23 26 ]. Since the distribution of the 2007 Global Fund to Fight AIDS, Tuberculosis and Malaria grant, artemisinin-based combinations are free nationwide and the NMEP has achieved 100% LLIN coverage in SeA [ 1 , 24 , 26 ]. Notwithstanding, unions with a high malaria incidence persist in Khagrachhari, Bandarban and Rangamati.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This has been shown previously [ 23 26 ]. Since the distribution of the 2007 Global Fund to Fight AIDS, Tuberculosis and Malaria grant, artemisinin-based combinations are free nationwide and the NMEP has achieved 100% LLIN coverage in SeA [ 1 , 24 , 26 ]. Notwithstanding, unions with a high malaria incidence persist in Khagrachhari, Bandarban and Rangamati.…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence to show that artemisinin-resistant malaria parasites have spread north- and westward from the Thai-Myanmar border [ 42 ]. There are concerns that migrants and refugees from these areas may import antimalarial resistant parasites [ 1 , 5 , 26 , 29 , 43 ]. In the case that antimalarial resistance spreads to Bangladesh, it may be more likely to propagate further into India, the country with the largest at-risk population and highest number of cases of malaria in the SEA Region [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate Change Cell , Bangladesh reported that, from 1984 to 1993 there were 301,651cases of malaria in Bangladesh, but from 1994 to 2003 it increased to 507,485 (68% increased incidence) [ 26 ]. Although after the introduction of artemisinin treatment and government and other partner organization lead massive drive for malaria elimination, the cases decreased to 1.4/1000 population in Bangladesh [ 27 ]. The same report revealed an increasing trend for diarrheal diseases, Kala-azar and skin diseases in three districts (drought-prone Rajshahi, flood-prone Manikganj and salinity-dense Satkhira) of Bangladesh between 1999 to 2005 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. falciparum remains the dominant malaria species in the country, however its proportion has dropped from 90% in 2007 to less than 80% in 2016, with a rising proportion of P. vivax cases [22][23][24][25]. As in many countries, PQ is provided for the radical cure of P. vivax, but patients are not tested for G6PDd to guide treatment and no systematic assessment of the prevalence of G6PDd within the country has been conducted.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%